The Function of Affixes in Augmented Triliteral Verbs of the Fa''ala Pattern in the Arba'in Hadith - Neng Nurmaltuffah; Ihin Solihin; Dayudin Dayudin (Hasanuddin University, 2026)
This study examines the role of affixes (al-lawāṣiq) in augmented triliteral verbs following the fa‘‘ala (فَعَّلَ ) pattern as found in Hadith Arba‘in An-Nawawiyah by Imam An-Nawawi. The main focus of this research is to identify the types and semantic functions of affixes within the verbal structures of Hadith Arba‘in and to explain their morphosyntactic roles. The study employs a qualitative descriptive approach using the distributional method (al-tawzī‘ī) through deletion and substitution techniques. The research data are derived from the original text of Hadith Arba‘in containing verbs in the fa‘‘ala pattern, such as ‘allama, ṣaddaqa, and raddada. The findings indicate that affixes in the fa‘‘ala pattern function to express transitivity (al-ta‘diyah), intensification or frequency (lil-takthīr), and removal or negation (lil-salb), which transform the characteristics of the base verb into stronger, causative, or repetitive meanings. This analysis demonstrates that affixation functions not only as a mechanism of word formation but also enriches the theological dimension of hadith meaning. The study confirms that the analysis of affix functions in augmented triliteral verbs of the fa‘‘ala pattern plays a crucial role in understanding the grammatical and semantic meanings of Hadith Arba‘in, and reveals the close relationship between Arabic morphological structure and the reinforcement of normative messages that are educational, moral, and spiritual in nature.